THERMAL METHODS OF BOTTOMHOLE FORMATION ZONE STIMULATION - Смоловик, Ліліана Романівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The article presents analysis of the results obtained from the study of face heating zones of the reservoir by pumping liquid coolant (water, hydrocarbon condensate) and the use of bottomhole electric heater in order to increase the temperature of oil. The optimum injection time of piping and volume of pumped coolant as well as the warm-up period and power of bottom-hole electric heater were found.